Study and results of reconstruction plating in fracture posterior column and posterior wall of acetabulum - Kachnerkar, Nilesh Indulal; Markade, Pravin (International Journal of Research in Orthopaedics, 2017)
Background: Posterior acetabulum fractures are the most common type of acetabular fractures. Acetabular fracture was an enormous orthopaedic problem in which the treatment was grossly inadequate and many patients were left with incapacitating pain. These fractures were often feared because of the poor outcome in many patients treated non-operatively. There are few published studies with a prolonged follow up. Thus this study was to review the displaced posterior acetabular fractures treated operatively in our hospital during last 5 years with regards to clinical, radiological results, the rate of surgical complication and the rate of successful fracture reduction. Methods: The patients with posterior acetabulum fractures were diagnosed on basis of clinical suspicion and confirmed on x-rays and CT scans. Displaced fractures were treated surgically in lateral position through Kocher-Langenbeck approach and fractures were fixed with reconstruction plates and cancellous screws and results studied. Results: Clinical grading was based on Merle d’Aubigne and Postel scoring which has been modified by Matta, According to this scale excellent to good results seen in 76.66% and fair results seen in 23.33% of cases. Radiological assessment grading according to the criteria developed by Matta, According to this criteria excellent to good radiological results are seen in 79.66% and poor results in 6.66% of cases. Conclusions: Displaced posterior acetabular fractures treated by open reduction and internal fixation with anatomical reduction allow early mobilisation and weight bearing and gives excellent results.